SAT0315 Imatinib-loaded targeted gold nanoparticles ameliorate experimental lung fibrosis induced by bleomycin. (15th June 2017) - Codullo, V; Breda, S; Meloni, F; Cova, E; Inghilleri, S; Colombo, M; Prosperi, D; Malatesta, M; Calderan, L; Montecucco, C; Distler, J
Abstract : Background: Systemic Sclerosis (SSc) is an autoimmune disorder frequently affected by an interstitial lung involvement (ILD) that significantly deteriorates long term outcomes. In previous experiments we proved that specifically engineered gold-nanoparticles (GNP) loaded with imatinib and targeted with an anti CD44 Ab (GNP-HCim) significantly inhibited proliferation and induced apoptosis of fibroblast-like cells derived from ILD-SSc patients [1]. In vitro, GNP-HCim showed higher efficacy compared to the drug alone. Objectives: To demonstrate in vivo the efficacy of GNP-HCim in ameliorating bleomycin-induced lung fibrosis Methods: Eight-week-old C57BL6 male mice (n=8/group) were assigned to either: (1) controls receiving intratracheal aereosolization of saline solution and unloaded functionalised GNP (GNP-HC); (2) mice treated with intratracheal instillation of bleomycin (50 uL) on day 0 and GNP-HC; (3) mice treated with bleomycin on day 0 plus GNP-HCim; (4) mice treated with bleomycin plus intraperitoneal (i.p.) Imatinib (50 mg/kg, once daily). GNP-HC or GNP-HCim were administered by intratracheal instillation on day 10–15–20–25 and 3 h before culling. All mice were sacrificed on day 28. Lung specimens were analysed by electron microscopy, immunohistochemistry and immunofluorescence (IF). Data were evaluated by 2 blind observers and analysed with GraphPrism software for statistics. Results: The administration of imatinib i.p or via GNP-HC reduced pathologic changes of the lungs as evaluated by the Lung Injury score and the Ashcroft score (p<0.05 for both). Collagen quantification by Picro Sirius Red revealed a significantly reduced staining only in the GNP-HCim group (p=0.0135 vs controls). IF revealed a significant reduction in αSMA+ myofibroblast counts when mice were inhaled with GNP-HCim (14.36±1.69/hpf) or injected i.p with imatinib (7.64±1.17/hpf) as compared to the controls (24.01±3.58/hpf, p=0.003 and p=0.0013 respectively). IF also showed significantly reduced counts of CD45+ (15.21±1.87/hpf vs 29±2.247/hpf in controls, p=0.0006) and CD44+ cells in groups treated with GNP-HCim (18.61±1.495) or imatinib i.p. (13.57±0.864), versus controls (28.56±2.854, p=0.0111 and p=0.0004 respectively). In imatinib i.p. and GNP-HCim-treated groups there was a significant reduction of phosphorylated c-Abl and PDGF-R, two downstream targets of imatinib, to levels comparable to group 1 controls with respect to the bleomycin group (p<0.05 for both). Finally, electron microscopy revealed accumulation of GNP-HCim and GNP in alveolar macrophages. Conclusions: In the experimental model of bleomycin-induced lung fibrosis imatinib delivered to lungs through inhalation of anti CD44 targeted GNP was as effective as imatinib administered by i.p. route. These data favour the use of GNP in the development of new therapeutic approaches to SSc-ILD, which might be associated to a lower toxicity and side effects of systemic treatment. References: Cova E, Ann rheum Dis 2016, 75(Suppl2): 61. Disclosure of Interest: None declared